2015
DOI: 10.1158/0008-5472.can-14-2103
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Drug Tolerance in Cancer Cell Populations: An Evolutionary Outcome of Selection, Nongenetic Instability, and Stress-Induced Adaptation

Abstract: In recent experiments on isogenetic cancer cell lines, it was observed that exposure to high doses of anticancer drugs can induce the emergence of a subpopulation of weakly proliferative and drug-tolerant cells, which display markers associated with stem cell-like cancer cells. After a period of time, some of the surviving cells were observed to change their phenotype to resume normal proliferation and eventually repopulate the sample. Furthermore, the drug-tolerant cells could be drug resensitized following d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
142
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 124 publications
(147 citation statements)
references
References 45 publications
4
142
0
1
Order By: Relevance
“…In [6], we showed that these models are capable of reproducing the main experimental observations detailed in [1]. Our analysis highlighted the important role of non-genetic fluctuations in phenotype in the emergence of drug tolerance in PC9 cancer cell lines.…”
Section: Main Results and Perspectivesmentioning
confidence: 57%
See 1 more Smart Citation
“…In [6], we showed that these models are capable of reproducing the main experimental observations detailed in [1]. Our analysis highlighted the important role of non-genetic fluctuations in phenotype in the emergence of drug tolerance in PC9 cancer cell lines.…”
Section: Main Results and Perspectivesmentioning
confidence: 57%
“…However, if appropriate future experimental evidence emerges for this system, such as time series data for proliferation rates or cell density, then this could be used to determine whether an additional mechanism, like stress-induced adaptation of the survival potential, should be added to the basic framework established in [6].…”
Section: Main Results and Perspectivesmentioning
confidence: 99%
“…At this stage, our model does not contain spatial structure, although it could be extended to include spatially distributed phenotypic attributes and migration of individuals at the cost of significantly increased complexity. Despite this simplification, analogous models have already been proven to be capable of shedding some light on the mechanisms which underlie patterns of evolution and adaptation in asexual populations [14][15][16][17][18][19]. From the mathematical point of view, our work follows earlier papers on the derivation of deterministic mesoscopic models from stochastic agent-based models [20][21][22][23][24][25] and the analysis of integrodifferential equations that arise in models of evolutionary dynamics within phenotype-structured populations [26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 98%
“…In order to address these questions, in [6] we proposed an Individual-Based (I-B) computational model [4,[7][8][9] and an Integro-Differential Equation (IDE) model [10][11][12] of the phenotype evolution observed in [1]. Such models can be used as in silico laboratories to test verbal hypotheses, and uncover mechanisms that underlie emergent features of cancer cell populations.…”
Section: Introductionmentioning
confidence: 99%